Clinical value of perivascular fat attenuation index and computed tomography derived fractional flow reserve in identification of culprit lesion of subsequent acute coronary syndrome - Huang, Minggang; Han, Tingting; Nie, Xuan; Zhu, Shunming; Yang, Di; Mu, Yue; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2023)
Abstract Purpose: To investigate the value of perivascular fat attenuation index (FAI) and coronary computed tomography angiography (CCTA) derived fractional flow reserve (CT-FFR) in the identification of culprit lesion that caused subsequent acute coronary syndrome (ACS). Methods: Thirty patients with documented ACS event who underwent invasive coronary angiography (ICA) from February 2019 to February 2021 and received CCTA in the previous 6 months were collected retrospectively. 40 patients with stable angina pectoris (SAP) were matched as control group according to sex, age and risk factors. The plaque characteristics, perivascular FAI and CT-FFR of 32 culprit lesions and 30 non-culprit lesions in ACS patients and 40 highest-grade stenosis lesions in SAP patients were statistically analyzed. Results: FAI around culprit lesions was increased significantly (-72.4±3.2 HU vs. -79.0±7.7 HU, vs. -80.4±7.0HU, all p<0.001) and CT-FFR was decreased for culprit lesions of ACS patients [0.7(0.1) vs.0.8(0.1), vs.0.8(0.1), p＜0.001] compared to other lesions. According to multivariate analysis, diameter stenosis (DS), FAI, and CT-FFR were significant predictors for identification of the culprit lesion. The integration model of DS, FAI, and CT-FFR showed the significantly highest area under the curve (AUC) of 0.917, compared with other single predictors (all p < 0.05). Conclusions: Integration of DS, FAI, and CT-FFR could significantly improve the performance of CCTA to identify the culprit lesions that subsequently lead to ACS.